A Simplified Algorithm to Estimate Latent Heating Rate Using Vertical Rainfall Profiles Over the Tibetan Plateau. Issue 2 (15th January 2019) - Li, Rui; Shao, Wencheng; Guo, Jingchao; Fu, Yunfei; Wang, Yu; Liu, Guosheng; Zhou, Renjun; Li, Wenzhuo
Abstract: In this study, a simplified semiphysical retrieval algorithm for latent heat (LH) released from precipitation over the Tibetan Plateau is derived and analyzed. The physical basis of this algorithm is that the vertical gradient of rain rate (−dR/dZ or Γ) represents the temporal rate of rain formation based on the steady state assumption, and the precipitation formation rate is closely related to the cloud formation rate, which is directly proportional to the latent heating rate. In this algorithm, the LH rate is represented as a linear function of Γ with fixed slope and intercept term determined by 3‐month Weather Research and Forecasting Model simulations over the Tibetan Plateau. Comparison to model results shows that the retrieval scheme can correctly capture the main features of LH horizontally and vertically. Comparison with results from other two widely accepted LH algorithms using Global Precipitation Measurement Dual Precipitation Radar real observations shows that this retrieval scheme generally agrees with them over low‐altitude areas but yields more convective‐type LH over the highlands with a relatively low heating center. This algorithm is specially designed for application to high altitudes. With this algorithm and the associated coefficients provided, researchers can readily do LH retrieval in their cases of interest by themselves. The only required input is the vertical profile of rain rate, which is available from current satellite precipitation radar observations. Key Points: A new latent heating retrieval algorithm is developed Validation and consistency check of the new algorithm are conducted The new algorithm has its advantage over Tibetan Plateau